Formulation and optimisation of topical preparation from malaysian honey for prevention and treatment of bacterial infection - Mohd Amir Shahlan, Mohd Aspar (2021)
The bacterial infection is the most common contamination on a wound. The use of antibiotics as a primary treatment is not always effective due to the emergence of antibiotic-resistance bacteria. Honey is one alternative plant by-product that can be used to prevent bacterial infection. While known to possess beneficial bioactive properties, including antibacterial, the effective use of Malaysian honey to prevent the growth of wound-associated bacteria is undetermined. Due to tropical rainforest, Malaysian honey owned high moisture content that unsuitable to be directly applied without improvement on its rheological properties. In an effort to make use of Malaysian honey in the treatment of the wound, this study aims to prepare the Malaysian honey as a topical antibacterial preparation by improving the rheological properties of the honey using xanthan gum and guar gum, which were independently used as the polymeric agents. Considering thorough antibacterial evaluation, the bacteriostatic and bactericidal effects against bacteria associated with wound infection of three Malaysian types of honey (kelulut, tualang, and acacia) were evaluated. In the effort to further understand the antibacterial properties of the honey, the factors of acidity, peroxide, and non-peroxide compounds that contribute to antibacterial properties of the honey were qualitatively identified. Response Surface Methodology (RSM) was used to optimise the antibacterial properties of the preparations. Once optimised, the optimal preparations were evaluated in terms of physicochemical properties, antibacterial efficacy, and stability. Based on the findings, kelulut, tualang, and acacia have been beneficial agents to prevent the growth of wound infection bacteria, supported by the existence of bacteriostatic effect against the bacteria at the concentration of 50% (w/v) and below. As for the bactericidal effect, kelulut was the only honey that exhibited bactericidal effect against all bacteria tested at the concentration of 50% (w/v) and below. The bactericidal effect was absent in tualang and acacia on certain bacteria, including Escherichia coli and Enterococcus faecalis. The antibacterial properties of kelulut were observed to be majorly due to acidity, followed by peroxide and non-peroxide compounds. Based on the potent antibacterial properties, kelulut was considered for the topical preparation which the optimal preparation was formulated at pH of 3.5, honey concentration of 90% (w/v), and polymeric agent of 1.5% (w/v). Xanthan gum was revealed as the recommended polymeric agent since the preparation using xanthan gum showed a larger inhibition zone by 1.2-fold compared to guar gum, indicating higher antibacterial properties. This was supported by the stable viscosity of the preparation using xanthan gum within six months of stability study, while a contradicting outcome was observed using guar gum with reduction in viscosity by 3.6-fold between initial (0 month) and final (6th month) measurement. In conclusion, among the Malaysian honey, kelulut was the most promising agent that can be used to inhibit the bacteria associated with wound infection. The study has successfully prepared the kelulut honey as a topical preparation using xanthan gum that resulted with stable and adequate physicochemical properties, without compromising on its antibacterial efficacy.